Adare-Tasiwoopa ápi, Sierra and Nathan K. Silva. Gamification in Higher Education: A How-to Instructional Guide. Routledge, 2024, 252 pages. - Willa Swift Black (Journal of the Assembly for Expanded Perspectives on Learning, 2024)
Gamification in Higher Education: A How-to Instructional Guide - A Review